The problems of biology - Maynard Smith, John, 1920- (Oxford ; New York : New York, 1986)
This introduction to the fundamental concepts of biology is unique in presenting modern ideas in terms that can be understood without previous knowledge of the subject.
"An OPUS book."
Includes index.
Bibliography: p. [125]-131.
Keywords: Biology; Biology -- Philosophy